2019
DOI: 10.1152/japplphysiol.00220.2019
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory adaptations with progressive heat acclimation are predominantly evident in uncompensable, but not compensable, conditions

Abstract: This study assessed whether, notwithstanding lower resting absolute core temperatures, alterations in time-dependent changes in thermoregulatory responses following partial and complete heat acclimation (HA) are only evident during uncompensable heat stress. Eight untrained individuals underwent 8 wk of aerobic training (i.e., partial HA) followed by 6 days of HA in 38°C/65% relative humidity (RH) (i.e., complete HA). On separate days, esophageal temperature (Tes), arm (LSRarm), and back (LSRback) sweat rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 55 publications
(113 reference statements)
1
30
0
Order By: Relevance
“…2016; Ravanelli et al . 2019), although this is not a consistent finding (Nadel et al . 1974; Roberts et al .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…2016; Ravanelli et al . 2019), although this is not a consistent finding (Nadel et al . 1974; Roberts et al .…”
Section: Discussionmentioning
confidence: 55%
“…1997; Ravanelli et al . 2019). These divergent observations could be related to the characteristics of the heat acclimation protocols employed (duration, passive vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WhileV O 2 max does not alter the thermoregulatory responses during exercise in compensable conditions (Jay, Bain, Deren, Sacheli, & Cramer, 2011), it is difficult to separate the influence of a higheṙ V O 2 max vs. repeated thermal stress on training-induced improvements in thermoregulatory capacity during uncompensable heat stress. For example, we recently demonstrated that 8 weeks of aerobic training increases maximum skin wettedness (Ravanelli, Coombs, Imbeault, & Jay, 2018), and increases local and whole-body sweat rates and reduces the change in core temperature by ∼0.2 • C during 60 min of uncompensable heat stress (Ravanelli, Coombs, Imbeault, & Jay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite inconsistencies around changes in skin blood flow, mechanistic studies have found HA to increase skin blood flow at a given core temperature in fixedintensity trials, helping increase the rate of heat dissipation [29,125,[134][135][136]. When wearing military clothing any HA-mediated increase in skin blood flow will likely be less effective in promoting heat loss than current research would assume but may still contribute to total heat loss and slow the rise in core temperature.…”
Section: Skin Blood Flowmentioning
confidence: 76%